The role of Salmonella in animal food - Jeffrey, Andrea (Kansas State University, 2016)
Salmonella contamination in animal food production facilities is a growing concern. The bacteria has been the cause of 40% of pet food recalls in the past 5 years, and there are potential human health implications because pet food is a direct human contact food. A potential method to reduce Salmonella contamination in pet food is through the use of acidifiers and desiccants to destroy and inhibit growth of bacteria. The objective of this thesis was to quantify Salmonella contamination in livestock feed and pet food manufacturing facilities, and propose mitigation measures to mitigate the presence of pathogens in animal food. Therefore, the objective of Experiment 1 was to investigate sources of Salmonella contamination throughout livestock feed (n = 2) and pet food (n = 2) manufacturing facilities on a specific sampling day. Salmonella was present in all four facilities. However, one of the livestock feed manufacturing facilities had more than double the Salmonella-positive locations than all other facilities. This experiment demonstrated that surface type and location should be taken into consideration when controlling Salmonella contamination. In Experiments 2 and 3, the use of a commercial powdered dry acidulant, sodium bisulfate, was studied as a coating of dog kibble to reduce and prevent Salmonella growth over time. The coating reduced Salmonella concentration, and its efficacy was not impacted by altering the bulk density or surface area of the kibble. Experiment 4 was conducted to determine the efficacy of sodium bisulfate added to poultry mash to reduce or prevent Salmonella growth over time. The inclusion of the dry acidulant did not reduce Salmonella concentration; however, storage time reduced Salmonella contamination in poultry feed. In summary, Salmonella contamination exists in manufacturing facilities, but the location and magnitude of contamination differs. Furthermore, sodium bisulfate effectively reduces Salmonella contamination when applied as a pet food coating, but not in poultry feed.
Keywords: Salmonella; Pet food; Sodium bisulfate; feed mill